A study of clinical profile of patients with CSOM attending tertiary care hospital - Muqtadir, Faiz; S., Rahul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Proper management of COM is significant because it is an important cause of middle ear disease. After complete history, thorough clinical examination, the disease is diagnosed. The persistent infection and resultant inflammatory responses are tackled with effective pharmacotherapy. Audiological assessment done by pure tone audiometry for air and bone conduction in order to evaluate and document. Methods: Total 50 patients diagnosed with CSOM attending the ENT OPD of Medical College were prospectively analysed. Patients fulfilling the selection criteria were included in the study after taking informed consent. All the patients in the study were clinically evaluated by taking detailed history and clinical examination including TFT, as per the proforma. Results: The mean age of our patients was 28.88 years, ranging from 16 years to 52 years; with almost 75% between 15 and 35 years. 20 patients each had CSOM in the right as well as left ear and 10 suffered from bilateral CSOM. Conclusions: Recurrent ear infection will cause hearing impairment over the years as a result of mucosal changes in the windows and ossicles.